Problems in Speaking Faced By EFL Students of Mulawarman University - Sayuri, Sayuri (Indonesian Journal of EFL and Linguistics, 2016)
Learning English ideally consists of four skills. They are listening, speaking, reading, and writing. All of them are interrelated from one another. Someone who masters four skills of English will be able to communicate in oral or written easily. In fact, speaking English is not easy. Speaking is an interactive process of constructing meaning that involves producing, receiving, and processing information. In this study, the researcher was interested in describing the problems in speaking faced by fourth semester students of English Department at Mulawarman University. Descriptive qualitative research was used as design of this study. The sample of this research consists of 24 students in the fourth semester. The data were obtained through the speaking test and questionnaire. Based on the speaking test and questionnaire, the students faced some problems related to pronunciation, fluency, grammar, and vocabulary. The questionnaire also showed additional findings where students faced other problems, namely not having self-confidence, shyness to speak, being afraid of making mistakes, feeling nervous, and having nothing to say. Next, there are some factors resulting problems of speaking to the students, firstly less of reading habit, uneven participation and English practice both inside and outside the classroom, and confusion on applying grammar rules.